AGE-RELATED FEATURES OF PERIPHERAL BLOOD MARKERS IN CHILDREN AND YOUNG ADULTS WITH NORMAL AND PATHOLOGICAL REMODELING OF BONE TISSUE - M. V. Dvornichenko; A. E. Sizikova; L. A. Dmitrieva; A. A. Khmel; T. V. Saprina; I. A. Khlusov (Бюллетень сибирской медицины, 2016)
Activities of total alkaline phosphatase (TALP) and its bone isoform (BALP) was greater in groups of children and adolescents in the late posttraumatic period (pattern of reparative bone remodeling) and scoliosis (pathological bone remodeling), than in the control (healthy children and adolescents). The content of collagen type I degradation products (CrossLaps) peripheral blood practically was unchanged. Examined group with posttraumatic period had high activity of tartrate-resistant acid phosphatase form (TRACP). TALP activity reached minimum values in all the studied groups. In the process of children growing to 15–18 years old, as compared to 7–10 years old, reducing activity of remodeling was observed under physiological (healthy donors) and reparative osteogenesis. It’s changes was recorded by significant decrease of the studied indicators. On the contrary, children 15–18 years old with scoliosis had maximum of the imbalance (activation/inhibition of various signs of osteogenesis) of resorptive/synthetic bone processes. Also, for this group we discovered decrease osteocalcin concentration of 4 times in comparison with the group children of 7–10 years old. The detected growth of the correlations number in the correlation matrix of bone remodeling markers in case of scoliosis proposes the reduction of adaptation reserve of 15–18 years old adolescents, suffering from dysplasia of connective tissue. Thus, the pathophysiological and clinical significance of distant markers of bone metabolism screening in peripheral blood the is ambiguous. The interpretation of these indicators is difficult and largely depends on the clinical situation and age of patients. This requires improving the diagnostic approach to assess physiological and pathological remodeling of bone tissue by means of biochemical blood indicators.